MENGIDENTIFIKASI KEMUKTABARAHAN TAREKAT SYAHADATAIN - Rosyid, Moh (ULUL ALBAB Jurnal Studi Islam, 2018)
This article discusses about Shahadatayn tarÃ®qah, one of lesser-known tarÃ®qah in Indonesia. The writer explores it from a primary source written by Abah â€˜Umar, the founder of this tarÃ®qah and other supporting references. To be a member of Shahadatayn tarÃ®qah, one is acknowledged through an inaugural ceremony (bayâ€˜at), á¸uhÃ¢Â and tahajjud praying in fourty days, reciting á¹£alawÃ¢tÂ tunjÃ®nÃ¢, wirid, AsmÃ¢â€™ NÃ»r al-ÃŽmÃ¢n, and AsmÃ¢â€™ al-á¸¤usnÃ¢. Shahadatayn is known for its uniqueness such as implementing the meaning of shahÃ¢dat in daily life, wearing white attire and turban when performing prayer, chanting after the obligatory prayers, á¸uhÃ¢, tahajud, and other sunna prayers. Shahadatayn tarÃ®qah is not as famous as the other tarÃ®qah as it has not been listed in the JATMAN as muâ€˜tabar version. This is because there is no murshid transformation from the Prophet Muhammad and continues through the path of the á¹£Ã¢lihÂ to the murshid. JATMAN version can not be an absolute reference for it is within the circle of NU and not all tarekat residents are NU members. Furthermore, the actual Shahadatayn has a murshid lineage, i.e. from Prophet Muhammad, Sharif Hidayatullah, and Abah â€˜Umar who is now passed on by his descendants. Although it is realized that the genealogy is not as many other tarÃ®qahs, but the content of his teachings is in line with the guidance of the Prophet Muhammad.